AC/DC building distribution network design and management – part I (to optimal the network design through AC/DC hybrid network) - Muhammad Zabid Mohamed Sulaiman (Nanyang Technological University, 2023)
The design and management of building circulation networks is essential for efficient energy use and cost reduction. With the increasing use of renewable energy sources and the need for more sustainable energy practices, it is essential to consider innovative answers for building dispersion network design and management. In this dissertation, we propose a crossover AC/DC network design way to deal with optimize building circulation networks. The proposed approach considers the advantages and constraints of both AC and DC networks and seeks to find an ideal balance between the two. AC networks have been the customary methodology for building conveyance networks, yet DC networks are gaining footing due to their higher efficiency and similarity with renewable energy sources. The cross breed approach will leverage the strengths of the two networks while minimising their constraints to achieve ideal network design. "An AC/DC half-breed conveyance network contains various voltage levels, DC lines, and converters, resulting in a mind-boggling activity mode and the need for an ideal booking methodology," the report states. For the AC/DC hybrid distribution network, this research proposes a simplified two-layer control structure comprising a transport control layer and a schedule management layer. This configuration enables the power electronic transformer's "energy routing" capability to be fully employed. The entire operating expenses of the AC/DC hybrid distribution network should be reduced during the scheduling cycle. This goal takes into account the characteristics of various distributed generators, the special design of the AC/DC hybrid distribution network, and the intricate interconnections between power sources, loads, and energy storage devices. The AC/DC half-and-half distribution network's optimal scheduling model is then constructed using a power electronic transformer. The open-source solution, which is capable of understanding the complete retention of renewable energy and the best coordinated control of "source-load-storage," validates the practicality of the optimal scheduling strategy.